2009
DOI: 10.1073/pnas.0907541106
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen management is essential to prevent tropical oil palm plantations from causing ground-level ozone pollution

Abstract: More than half the world's rainforest has been lost to agriculture since the Industrial Revolution. Among the most widespread tropical crops is oil palm (Elaeis guineensis): global production now exceeds 35 million tonnes per year. In Malaysia, for example, 13% of land area is now oil palm plantation, compared with 1% in 1974. There are enormous pressures to increase palm oil production for food, domestic products, and, especially, biofuels. Greater use of palm oil for biofuel production is predicated on the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
160
2
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 167 publications
(175 citation statements)
references
References 11 publications
(6 reference statements)
10
160
2
2
Order By: Relevance
“…In all scenarios for future energy supply, fuels from biomass -so-called biofuels -and/or other energy sources from biomass, play an important role (Demirbas, 2008). Recent comprehensive analyses (Hewitt et al, 2009) demonstrated that conversion of tropical rainforest to oil palm plantations in Malaysia results in enhanced isoprene emission that lead to O 3 formation.…”
Section: Discussionmentioning
confidence: 99%
“…In all scenarios for future energy supply, fuels from biomass -so-called biofuels -and/or other energy sources from biomass, play an important role (Demirbas, 2008). Recent comprehensive analyses (Hewitt et al, 2009) demonstrated that conversion of tropical rainforest to oil palm plantations in Malaysia results in enhanced isoprene emission that lead to O 3 formation.…”
Section: Discussionmentioning
confidence: 99%
“…Even the VOC produced by natural rainforest can lead to harmful concentrations of ozone if NO x mixing ratios are allowed to enter the multi-ppbv range such as that found in rural Western Europe, North America and continental Asia [49,50]. VOC emissions from oil palm plantations, when combined with NO x concentrations typical of rural areas in the developed world, lead to potential peak ozone concentrations similar to those owing to heavy urbanization (not shown), indicating that significant air-quality issues may accompany large adoption of this crop in future unless tropical background NO x emissions are controlled [2]. However, not all crops have such potentially harmful effects on ozone formation.…”
Section: Ozone Changes-the Response To Changes In Local Emissions (A)mentioning
confidence: 99%
“…Production for the global food industry has been one of the major drivers. Biofuels have been seen as environmentally friendly alternatives to fossil fuels but in recent years various questions have been raised about some potential negative impacts on greenhouse gas concentrations [16] and on air quality [2]. Analysis of all the stages relevant to these technologies are necessary and OP3 has provided some important new information on emissions and atmospheric chemistry.…”
Section: Tropospheric Ozone and Land-use Changementioning
confidence: 99%
See 1 more Smart Citation
“…Typical woody biofuel species are willow, eucalypt and oil palm, all of which have substantial rates of isoprene emissions that likely exceed emissions of local vegetation. Largescale conversion of tropical rainforest into oil palm plantations in areas of high (or projected to increase) NO x emissions of SE Asia therefore has the potential to be detrimental for local O 3 levels (Hewitt et al, 2009). At the same time will an increase in agricultural versus forest area also affect emissions of oxygenated BVOC (methanol, acetaldehyde; Chung et al, 2002;Goto et al, 2008).…”
Section: Biological Emission Of Reactive Carbon and Nitrogenmentioning
confidence: 99%